Challenges and lessons learned from the Pediatric Heart Network Normal Echocardiogram Database study. (17th March 2020) - Truong, Dongngan; Lopez, Leo; Frommelt, Peter C.; Stelter, Jessica; Ni, Brenda; Cohen, Meryl S.; Prakash, Ashwin; Colan, Steven D.; Spurney, Christopher; Soslow, Jonathan; Pearson, Gail D.; Mahgerefteh, Joseph; et al.
Abstract: Background: The Pediatric Heart Network Normal Echocardiogram Database Study had unanticipated challenges. We sought to describe these challenges and lessons learned to improve the design of future studies. Methods: Challenges were divided into three categories: enrolment, echocardiographic imaging, and protocol violations. Memoranda, Core Lab reports, and adjudication logs were reviewed. A centre-level questionnaire provided information regarding local processes for data collection. Descriptive statistics were used, and chi-square tests determined differences in imaging quality. Results: For the 19 participating centres, challenges with enrolment included variations in Institutional Review Board definitions of "retrospective" eligibility, overestimation of non-White participants, centre categorisation of Hispanic participants that differed from National Institutes of Health definitions, and exclusion of potential participants due to missing demographic data. Institutional Review Board amendments resolved many of these challenges. There was an unanticipated burden imposed on centres due to high numbers of echocardiograms that were reviewed but failed to meet submission criteria. Additionally, image transfer software malfunctions delayed Core Lab image review and feedback. Between the early and late study periods, the proportion of unacceptable echocardiograms submitted to the Core Lab decreased (14 versus 7%, p < 0.01). Most protocol violations were from eligibility violations and inadvertent protected health information disclosure (overall 2.5%). Adjudication committee reviews led to protocol changes. Conclusions: Numerous challenges encountered during the Normal Echocardiogram Database Study prolonged study enrolment. The retrospective design and flaws in image transfer software were key impediments to study completion and should be considered when designing future studies collecting echocardiographic images as a primary outcome.